Constructed wetlands for degrading industrial effluents - Pearson, Samantha (My University, 2021)
Human and environmental exposure to chemical compounds, specifically aquatic environments are becoming more of a concern as environmental degradation continues. The release of polyphenolic compounds into the environment is of major concern as they are not easily broken down and persist for long periods of time exerting toxic effects on both human and wildlife. Constructed wetlands are being considered in South Africa, as an environmentally friendly alternative industrial wastewater treatment technology and are low in capital costs and require less maintenance and infrastructure than other treatment technologies. The pulp and paper industry is one of the biggest industries in the world, producing an effluent that is phenol-rich. This study looks at pulp and paper mill (phenol-rich) effluent remediation by constructed wetlands on a laboratory-scale. There are three main parts to this study on the use of constructed wetlands for phenol rich remediation: batch operation, continuous operation and phenol remediation kinetics. Batch operation investigated the most effective type of emergent macrophyte species as well as the effect pulp and paper mill effluent strength had on the phenol remediation efficiency. Continuous operation used a pure phenol solution to determine the most effective constructed wetland macrophyte configuration for effluent remediation and investigated the phenol and carbon oxygen demand concentration gradients along the length and depth of the constructed wetland bed for pure phenol solution and a full-strength pulp and paper mill effluent. The third phases, kinetics, investigated the approximate phenol remediation kinetics in both batch and continuous operation. It was found that different emergent macrophytes species do have an influence on the effluent remediation process and a full-strength pulp and paper (phenol-rich) effluent can be remediated by constructed wetlands in both batch and continuous operation with phenol remediation kinetics favoring warmer temperatures
A dissertation submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Engineering, 2021